Determination of Optimum Programmed Temperature for Fatty Acid Analysis of Chlorella Microalgae Extract Using GCMS Instrument - surani surani; Cahyo Pujiasmoro; Asep Kadarohman (Unesa Journal of Chemistry, 2023)
Gas Chromatography-Mass Spectrometry (GCMS) column temperature is one of the variables that must be considered in the analysis of chemical compounds, so that the compounds are appropriately separated. This study aims to determine the optimum programmed temperature for fatty acid analysis using the GCMS instrument. The fatty acid samples used were derived from the extract of Chlorella microalgae. Chlorella microalgae extraction was done by sonication for 60 minutes using hexane as solvent. The GCMS programmed temperature variations were carried out, namely the temperature increase was 5 OC /minute, 7 OC/minute, 9 OC/minute, 12 OC/minute with an initial temperature of 80 OC and a final temperature of 270 OC. The number of samples injected was 0.2 mL. The data from the analysis is processed by comparing the retention time and analysis time. It was found that the optimum condition for the programmed temperature measurement was the initial temperature of 80 oC and an increase of 9 OC/minute to a temperature of 270 OC with an analysis time of 21.1 minutes. The fatty acids in Chlorella microalgae extract are palmitic acid, oleic acid and stearic acid. By using this measurement method, the analysis time is shortened and the expected compounds can be identified properly Keywords: Analysis, GCMS, programmed temperature, fatty acids, Chlorella microalgae